The Effect of Complementary Interventions on Reducing Blood Pressure in Dual Role Women Suffering from Hypertension - Septianingtyas, Maya Cobalt Angio; Juwariyah, Siti; Jona, Resa Nirmala; Sovianti, Vivi (Journal of Language and Health, 2024)
Hypertension is a circulatory system that causes an increase in blood pressure above normal values with an increase in systolic blood pressure of more than 140 mmHg and diastolic blood pressure of more than 90 mmHg. The study was conducted at the Bandarharjo Health Center. The purpose of this study was to determine the effect of complementary interventions on reducing blood pressure in dual role - women suffering from hypertension sufferers. This study was conducted on April 24 - May 10, 2024. This study used quasi-experimental research with a one-group pre-post-test design. The number of samples in this study was 66 respondents with a simple random sampling data collection technique. This study used an observation sheet measuring instrument containing the characteristics of the respondents and blood pressure. The data collection procedure begins with a pre-test by measuring the respondent's blood pressure, then the researcher provides intervention in the form of complementary foot massage and therapy classical music, and lemon aromatherapy in combination. At the end of the study, the researchers conducted a post test by measuring the respondents' blood pressure. Results: The statistical test of this study used the Wilcoxon Test with a significance level (<0.05). The results of the statistical test of this study obtained a p-value of 0.0001. Based on the results of the p-value in the post-test, it can be concluded that there is an effect of complementary interventions on reducing blood pressure in dual role - women suffering hypertension.